Spatio-temporal dynamics of urban ecological services: A site-specific study of urban and peri-urban areas of Darjeeling Himalaya and Terai region, West Bengal, India - Shrabanti Dutta; Narender Verma (National Geographical Journal of India, 2024)
Urban ecosystems play a pivotal role in supporting human life by providing essential ecological services. In the present study, an attempt has been made to analyze the spatio-temporal dynamics of urban ecological services in terms of demand and supply patches during the last two decades from 2004 to 2022 over the urban and peri-urban areas of Darjeeling Himalaya and Terai region, West Bengal. 4 urban centers (Darjeeling, Kalipong, Kurseong, and Mirik) of Darjeeling Himalaya and 1 urban center (Siliguri) of the Terai region have taken into account for the study. Municipal boundaries of all the regions along with 2 km buffer zones are considered as urban and peri-urban regions respectively. Results revealed that all the study regions (Darjeeling, Kalimpong, Kurseong, and Siliguri) have shown an increase in both “demand” and “supply” patches except Mirik, which has experienced a decline in “supply” patches during 2004-2022. The highest increase in demand patches has been observed for Siliguri (169%) and lowest increase for Mirik (4.9%); while highest increase in supply patches is noticed for Darjeeling (80.4%). Geographical location of the urban centers has indirectly played a significant role behind this areal extension of demand and supply patches. In a nutshell, the increase of both “demand” and “supply” patches at the cost of reduction in “others” patches, indicated an equilibrium state of urban ecological services in the study regions.